2018
DOI: 10.2478/romneu-2018-0053
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics as an Indicator of Offending Vessel in Trigeminal Neuralgia and Hemifacial Spasms

Abstract: Context: Newer Imaging tool for diagnosing offending vessel in trigeminal neuralgia (TN) and Hemifacial spasms (HFS). Aim: To find out if Computational FluidDynamics (CFD) can correctly predict the offending vessel in HFS and TN & thus improving the outcome of Microvascular Decompression) MVD. Settings and Design: CFD is a relatively new mode of imaging. Its application to indicate offending vessel in TN & HFS was tested. Materials & Methods: Retrospectively we studied 13 consecutive patients opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Recent studies have indicated the involvement of CFD in neurovascular compression syndrome. 12 13 14 Satoh et al retrospectively analyzed the offending artery of 20 symptomatic TN and hemifacial spasm patients. They reported a relatively high magnitude of WSS at NVC compared with the surrounding site of NVC.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated the involvement of CFD in neurovascular compression syndrome. 12 13 14 Satoh et al retrospectively analyzed the offending artery of 20 symptomatic TN and hemifacial spasm patients. They reported a relatively high magnitude of WSS at NVC compared with the surrounding site of NVC.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated the involvement of CFD in neurovascular compression syndrome. 2527) Satoh et al 26) retrospectively analyzed the offending artery of 20 symptomatic TN and hemifacial spasm patients and reported a relatively high magnitude of WSS and restriction of WSS directional movement along the NVC compared with the surrounding site of NVC. According to this study, a high WSSR, which indicates focal elevation of WSS at the NVC site, has the potential to identify symptomatic compressions.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike recent CFD studies using computed tomography angiogram for the construction of artery models, 2527) the CFD technique used in this study is based on non-contrast-enhanced preoperative MRI, which is a simple and completely non-invasive method that provides useful information about the pathogenicity of NVC. This CFD technique should be considered during preoperative simulation of MVD.…”
Section: Discussionmentioning
confidence: 99%